Multi-UAV encirclement training optimization method based on implicit curriculum experience partitioning - Ling, Y. H. (Инноватика-2025 : сборник материалов XXI Международной школы-конференции студентов, аспирантов и молодых ученых, 28-30 апреля 2025 г., г. Томск, Россия)
This paper proposes an implicit curriculum learning framework for multi-drone coordination, employing autonomous phased training via dynamic experience replay. By integrating stage-critical sample prioritization and role-adaptive exploration policies, the method resolves local-global strategy conflicts without manual curriculum design. Validated in dynamic environments, the framework demonstrates enhanced collaborative efficiency and hierarchical strategy learning capabilities, providing systematic solutions for phased multi-agent tasks.